Intrinsic motivations on the development frontline: Do they exist? Do they endure? - Barr, A; Lindelow, M; Garcia-Montalvo, J; Serneels, P (GPRG, 2005)
Are new recruits to the development frontline intrinsically motivated in a way that may prevent them from becoming unproductive or corrupt? And are they likely to remain thus motivated as their careers progress? We seek answers to these questions using both survey and experimental data relating to a sample of Ethiopian nursing and medical students. We find that, according to four, arguably salient measures, the majority of the students are intrinsically motivated. We also find evidence that intrinsic motivations are socially rather than individually determined, may change as individuals’ social contexts change and may be eroded by exposure to an environment in which unproductive behaviour is endemic.